Comparative morphological analysis of compound eye miniaturization in minute hymenoptera. Issue 1 (January 2015) - Makarova, Anastasia; Polilov, Alexey; Fischer, Stefan
Abstract: Due to their small size, diminutive parasitic wasps are outstanding subjects for investigating aspects of body miniaturization. Information on minute compound eyes is still scarce, and we therefore investigated eye morphology in one of the smallest known hymenopteran species Megaphragma mymaripenne (body size 0.2 mm) relative to Anaphes flavipes (body size 0.45 mm) and compared the data with available information for Trichogramma evanescens (body size 0.4 mm). The eyes of all three species are of the apposition kind, and each ommatidium possesses the typical cellular organization of ommatidia found in larger hymenopterans. Compound eye miniaturization does not therefore involve a reduction in cell numbers or elimination of cell types. Six size-related adaptations were detected in the smallest eyes investigated, namely a) a decrease in the radius of curvature of the cornea compared with larger hymenopterans; b) the lack of extensions to the basal matrix from secondary pigment cells; c) the interlocking arrangement of the retinula cell nuclei in neighboring ommatidia; d) the distal positions of retinula cell nuclei in M. mymaripenne ; e) the elongated shape of retinula cell pigment granules of both studied species; and f) an increase in rhabdom diameter in M. mymaripenne compared with A. flavipes and T. evanescens . The adaptations are discussed with respect to compound eye miniaturizations as well as their functional consequences based on optical calculations. Graphical abstract: Highlights: The eye ultrastructure of one of the smallest known hymenoptera was investigated for the first time. Miniaturization of compound eye does not involve any reduction in cell numbers or cell types. Size-related adaptations in compound eyes were detected and discussed.